Knowledge Management Applications in Johannesburg Water’s Call Centre - Ruplal, Suchithra (My University, 2012)
Call Centres are viewed more and more as important and powerful means through which companies can improve service delivery to their customers. This research paper investigates how the strategic application of knowledge management within the Call Centre customer interface, through the support of senior management, can improve service delivery within Johannesburg Water. One-on-one interviews were conducted with selected Call Centre team leaders, and management from the Call Centre and the Operations department. Primary data was also extracted from the company‟s information management system (IMS). The Customer Service Representatives (CSRs) were observed within their work environment. Appendix A describes an example of the Call Centre customer service interface when a customer calls to log a complaint with Johannesburg Water, a Municipal Owned Entity (MOE). Knowledge management when applied as part of the Customer Relationship Management (CRM) strategy may be helpful in improving service delivery. Call Centre management has to invest in its people component of Knowledge Management (KM) strategy in order to have effective processes and effective technologies. Research conducted may be applicable and adapted to other public sector Call Centres. The study conducted indicates that senior management should focus on strengthening the “people” component of KM in order to achieve effective service delivery. Knowledge management gaps at the Call Centre were identified through the study which would be beneficial to Call Centre management in improving service effectiveness of the Call Centre for the organisation
MM thesis - P&DM
Keywords: Knowledge management; Call centres